Aerosols and global change in the Pyrenees - Jorge Pey; Javier Bandrés; Blas L. Valero-Garcés; J. I. López-Moreno (Mètode Science Studies Journal: Annual Review)
We have been witnessing rapid climate change in recent decades, with heatwaves now more frequent and winters less distinct. One notable consequence is the increasing frequency of dust storms in many areas of Spain. This raises concerns about the extent of atmospheric pollution compared to the past and its impact on regions like the Pyrenees. Current research aims to understand if dust episodes are more intense and frequent than before, how they affect high-altitude lakes, and how desert dust aerosols influence snow-cover duration in the area. These investigations are crucial for assessing the broader environmental impacts of climate change in mountainous regions.